2009
DOI: 10.1007/s10562-009-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multiple Promotion of the Direct Synthesis Contact Mass with P, Zn, and Sn on the Synthesis of Methylchlorosilanes

Abstract: The Direct Synthesis, or Rochow Synthesis, involves the reaction of methyl chloride, CH 3 Cl (MeCl), with Cu-Si contact masses (promoted with 1-2% of Zn, Sn, and P) to form methylchlorosilanes. Flow reactor studies (1 bar MeCl at 300°C) showed that contact masses promoted with Zn, Sn, and P (triply promoted) demonstrated the highest Si and MeCl conversion at early reaction times. In situ infrared spectroscopy suggested that in contrast to the doubly promoted catalysts (where CH 3 groups were primarily bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…However, when the addition was dropped to several hundred ppm of coppers, the promoting effect began to show up . Many researchers found that Sn has a promoting effect synergistically with Zn by reducing the melting points and surface tensions of Cu 3 Si, thus increasing surface transfer of Cl and accelerating formation of the active SiCl x sites . Sn‐promoted Cu can increase the concentration of surface methyl species .…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
“…However, when the addition was dropped to several hundred ppm of coppers, the promoting effect began to show up . Many researchers found that Sn has a promoting effect synergistically with Zn by reducing the melting points and surface tensions of Cu 3 Si, thus increasing surface transfer of Cl and accelerating formation of the active SiCl x sites . Sn‐promoted Cu can increase the concentration of surface methyl species .…”
Section: Chemistry: State‐of‐the‐artmentioning
confidence: 99%
“…The composite of Cu x Ag nanoparticles can be easily controlled by adjusting the ratio of metal precursors. These bimetallic Cu x Ag (such as Cu 50 Ag, Cu 20 Ag, Cu 10 Ag, Cu 5 Ag, CuAg, and CuAg 2 ) nanoparticles are used as model catalysts for Rochow reaction. Compared with the Si conversion for monometallic Cu (35.4% for Cu) and Ag (0% for Ag) nanoparticles, these bimetallic Cu x Ag nanoparticles exhibit much enhanced Si conversion (65.4% for Cu 50 Ag, 68.6% for Cu 20 Ag, 71.1% for Cu 10 Ag, 73.0% for Cu 5 Ag, and 70.3% for CuAg), demonstrating the synergistic electronic effect between Cu and Ag atoms in the AgCu bimetallic nanoparticles, which led to the lower electron density for Cu atoms, in the Rochow reaction.…”
Section: Introductionmentioning
confidence: 99%
“…XRD patterns for samples Cu, Cu50 Ag, Cu 20 Ag, Cu 10 Ag, Cu 5 Ag, CuAg, CuAg 2 , and Ag nanoparticles.…”
mentioning
confidence: 99%
“…1,2 In this reaction, gaseous methyl chloride (MeCl) reacts with silicon (Si) in the presence of Cu-based catalysts as following: [3][4][5] Among these products, dimethyldichlorosilane ((CH 3 ) 2 SiCl 2 , M2) is the most important monomer for the production of organosilane products in industry. 1,2 In this reaction, gaseous methyl chloride (MeCl) reacts with silicon (Si) in the presence of Cu-based catalysts as following: [3][4][5] Among these products, dimethyldichlorosilane ((CH 3 ) 2 SiCl 2 , M2) is the most important monomer for the production of organosilane products in industry.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, a high M2 yield is always demanded. 5,14 In the past few years, porous cubic structures such as Cu microparticles, 15 mesoporous Cu 2 O microspheres, 10 flower-like, 16 and hierarchical dandelion-like 5 Copper nitrate trihydrate (Cu(NO 3 5,14 In the past few years, porous cubic structures such as Cu microparticles, 15 mesoporous Cu 2 O microspheres, 10 flower-like, 16 and hierarchical dandelion-like 5 Copper nitrate trihydrate (Cu(NO 3 …”
Section: Introductionmentioning
confidence: 99%